Diametral Methodology: A Biographical Narrative of a PAI Teacher’s Shift from Fundamentalism to Pluralism in Aqidah Teaching - Siti Roudhotul Jannah; Fatqur Rohim; Wahyu Eko Purwanto; Idris Efendi; Wahyu Dewi Utari (CV. Creative Tugu Pena, 2025)
Education (PAI) teacher who experiences a profound methodological and ideological transformation from fundamentalism to pluralism in the context of aqeedah teaching. The transformation is examined through the framework of diametral methodology, a narrative research approach that situates opposing ideological poles as a dialectical space for understanding how epistemic, spiritual, and pedagogical changes unfold across time. By reading the teacher’s life history through this diametral lens, the study seeks to reveal the dynamic processes that shape pedagogical orientation, identity formation, and instructional decisionmaking in Islamic education. The data for this study are fictional yet academically grounded, constructed through a triangulation of literature on religious moderation, critical pedagogy, transformative learning theory, and the sociocultural experiences of Islamic education teachers in Indonesia. This approach enables the narrative to remain analytically rigorous while presenting a realistic and contextually rich portrayal of a teacher’s ideological journey. The findings illustrate that the teacher’s shift toward pluralism does not emerge abruptly; instead, it develops gradually through a series of existentialreflective crises, interfaith dialogues, exposure to diverse theological discourses, and increasing engagement with contemporary educational paradigms that emphasize inclusivity and human dignity.